Analysis Connection Mathematical Student through Learning Styles Think Talk Write (TTW) Tips Collaboration - Nufa visca amaratya; Putri indah lestari (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study aims to analyze students' mathematical connections through the application of the Think Talk Write (TTW) learning style and collaboration in the context of mathematics learning. The Think Talk Write (TTW) method emphasizes developing critical thinking, communication and writing skills in understanding mathematical concepts. Collaboration between students is also integrated to strengthen mathematical understanding through discussion and joint problem solving. This research uses a qualitative approach with case studies as the analytical framework. Data was collected through classroom observations, interviews with students, and analysis of students' writing. Research findings show that implementing the Think Talk Write (TTW) method with collaboration can improve students' mathematical connections, strengthen conceptual understanding, and improve communication and mathematical problem solving skills. Pedagogical implications of these findings are discussed to promote more effective and inclusive mathematics learning practices.